Effects of physical activity on symptoms of depression and anxiety in adults with alcohol use disorder (FitForChange): Secondary outcomes of a randomised controlled trial. (1st October 2022) - Welford, Paul; Gunillasdotter, Victoria; Andréasson, Sven; Hallgren, Mats
Abstract: Purpose: To compare the effects of yoga, aerobic exercise, and usual care on anxiety and depressive symptoms in non-treatment seeking adults with AUD. Method: Parallel, three-group, open-label randomised (1:1:1) controlled trial with blinded follow-up assessment. Non-treatment seeking adults (aged 18–75 years) were recruited via advertisements in a free newspaper in Stockholm, Sweden. All participants had clinician-diagnosed AUD prior to randomisation. This trial excluded those who were physically active, or for whom supervised physical activity was contraindicated. Participants were randomly assigned to 12-weeks of aerobic exercise, yoga, or usual care (telephone counselling). The secondary outcome of interest was the Hospital Anxiety and Depression Scale (HADS), assessed at baseline and 12-week follow-up. Primary analyses consisted of linear regression models and followed intention-to-treat (ITT) principals. Results: In total, 140 participants (mean age 53.7 years, SD=11.8) were recruited. Follow-up was completed for 42/45 participants randomised to TAU, 42/49 to aerobic exercise and 43/46 to yoga. ITT analyses included 126 trial participants. There were statistically significant within-group improvements in total HADS in all three intervention groups. Effect sizes for usual care and aerobic exercise were small (Hedges' g =0.48, 95% CI=0.16, 0.80 and g =0.41, 95% CI=0.09, 0.72, respectively), while yoga was associated with a large treatment effect ( g =1.06, 95% CI=0.69, 1.43). There were significant between-group differences in these improvements favouring yoga ( B =−2.15, 95% CI=−4.16, −0.15, p  = .035) relative to usual care, but no significant differences between yoga and aerobic exercise. No injuries were reported. Conclusions: Findings support the recommendation of yoga for non-treatment seeking adults with AUD. Highlights: This is the first RCT to examine the effects of yoga on symptoms of depression and anxiety in adults with AUD. In total, 140 participants with clinician-diagnosed AUD were included (90% retention). Yoga leads to improvements in anxiety and depressive symptoms; superior to those associated with usual care.